"You Don't Know Me": Polite Racism, Cultural Capital, and Afro-Caribbean Identity in Multicultural Canada - Coen-Sanchez, Karine (Université d'Ottawa / University of Ottawa, 2025)
This thesis examines identity formation and mobilization of social and cultural capital among first- and second-generation Haitian and Jamaican communities in Canada. Drawing on critical race theory, intersectionality, and sociological theories of cultural capital, it integrates Tara J. Yosso's model of community cultural wealth with the concepts of polite racism, racial ignominy, and duplicity of consciousness. These concepts articulate how subtle yet systemic racial exclusion - particularly in education and the labour market - undermines Afro-Caribbean cultural assets while upholding a veneer of multicultural inclusivity. The research reconceptualizes Blackness in Canada as a dynamic and contested identity, shaped by both historical legacies and contemporary systemic barriers. Through focus groups and in-depth interviews with Haitian and Jamaican participants in the Ottawa-Gatineau region, the thesis explores how cultural capital is leveraged to assert identity, resist stereotypes, and negotiate belonging across generations. Key findings demonstrate that cultural and social capital are not merely tools of social mobility but also sites of resistance and self-definition. First- and second-generation participants differ in their navigation of identity, highlighting a generational negotiation between cultural retention and adaptation, often under the pressure of systemic expectations. This negotiation is captured through the concept of duplicity of consciousness, which describes the lived tension between authenticity and assimilation in racialized contexts. The implications extend beyond academia, offering concrete policy recommendations for Canadian educational institutions and labour markets to better recognize and support the cultural wealth of Afro-Caribbean communities. In doing so, this research advances a more inclusive understanding of Blackness and multiculturalism in Canada.
Keywords: Afro-Caribbean identity; Cultural capital; Polite racism; Community cultural wealth; Intersectionality; Blackness in Canada; Racial capitalism